Pengujian Sifat Psikometri Skala Relational Aggression (RA) Versi Indonesia: Rasch Measurement Tool - Yuda Syahputra; Afdal Afdal (Cenderawasih Journal of Counseling and Education, 2022)
This study aims to validate by measuring the psychometric properties of the Indonesian version of the Relational Aggression (RA) scale. The study used a survey method and was collected from December 2019 to January 2020 and involved 241 participants in Indonesia (14 to 18 years). In this study the Rasch model was used to measure the psychometric properties of 17 RA items, with the help of WINSTEPS 3.73. The results of this study indicate that RA fulfills the psychometric measurement aspect by providing evidence as a valid and reliable instrument, with a very good item reliability value (.98) and sufficient person reliability (.75), and a Cronbach alpha value (KR-20) of (.81), meaning that the quality of the items is very good for revealing relational aggression. Furthermore, the results are reinforced by the Principal Component Analysis (PCA) value of the residual of 45.2%, meaning that the items in RA are representative for measuring relational aggression. The implications of this RA research can be accepted by researchers for collecting data or information related to the problem of relational aggression in Indonesia.